Effects of Improving Health Status on Testicular Development of Guinea Fowl (Numida meleagris) Reared under Natural Photoperiod in the Sudanian Zone of Burkina Faso - Hien, Ollo Cherubin; Diarra, Boureima; Brillard, Jean-Pierre; Boly, Hamidou; Sawadogo, Laya (International Journal of Poultry Science, 2011)
This study concerns the effect of improving health status on testicular development of local guinea fowl reared under natural photoperiod. Two groups of 100 males of guinea fowls chicks were used for the study. One group (T1) served as control and did not received any treatment while the second group (T2) received several treatments including anti-stress, trichonomacid, anticoccidies, dewormer and vaccination against New Castle disease. Results showed no difference in body weight at 28 weeks of age between the 2 groups. However at 24 weeks of age birds in T2 had higher values for mean testicle weight (286±70 versus 148±34 mg). Parameters for seminiferous tubes were also higher for T2 birds: mean volume (74±0.3 versus 63±6.6% of testicle volume), mean diameter (126±24 versus 89±13 μ) and mean length (6.4±0.4 versus 5.1±1 mm). Improved health status also increased population numbers of spermatocytes I, rounds spermatides and interstitial cells. Differences were significant at 20 weeks of age for Sertoli cells. Spermatogenesis starts at 24 weeks of age for T2 birds but at 28 weeks for T1 birds.